Flammable and Thermal Analysis of Biodiesel Blends at Different Composition - Ahmad Farid, Muhammad Nazrin (Universiti Teknologi PETRONAS, 2016)
his project was done to investigate and determine the flash point data and oxidation temperature of different biodiesel blends. Among the biodiesel blends being investigated in this project are biodiesel, diesel 45%-biodiesel 45%-methanol 10% (BDM10), diesel 40%-biodiesel 40%-methanol 20% (BDM20), diesel 45%-biodiesel 45%-ethanol 10% (BDE10) and diesel 40%-biodiesel 40%-ethanol 20% (BDE20). The flash point experiment is done using Eralytics flash point analyzer while the oxidation temperature experiment was done using Differential Scanning Calorimetry (DSC) equipment. For the flash point experiment it was determined that pure biodiesel has the highest flash point compared to other biodiesel blends thus it is the safest to produce and store in a bio refinery.